2014
DOI: 10.1016/j.jhin.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving the timeliness of meticillin-resistant Staphylococcus aureus antimicrobial decolonization therapy administration: a descriptive account

Abstract: SummaryBackgroundIt is important to ensure that the timely administration of appropriate antimicrobial decolonization therapy occurs when patients are identified as meticillin-resistant Staphylococcus aureus (MRSA)-colonized. Computerized Provider Order Entry (CPOE) with embedded Clinical Decision Support (CDS) may help to facilitate this.AimTo investigate changes in the average time from patient admission to administration of MRSA decolonization antimicrobial therapy in the context of various national and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Most evidence came from specialty settings (such as intensive care, emergency medicine and paediatrics); and from high‐risk patient groups (e.g. those at risk for or with infections); and from tertiary care …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most evidence came from specialty settings (such as intensive care, emergency medicine and paediatrics); and from high‐risk patient groups (e.g. those at risk for or with infections); and from tertiary care …”
Section: Resultsmentioning
confidence: 99%
“…We found that most work has been conducted in relation to CPOE and CDS systems, focusing on interventions that targeted individual prescribers through prompts and reminders …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitation of spread of infection depends on rapid and effective microbiological diagnostics, as in MRSA screening with responses within a few hours [50,51].…”
Section: Background Informationmentioning
confidence: 99%
“…The interoperability and automation of health information technology systems aim to minimise the time from the diagnostic order to the patient receiving the first dose. 26 During prescription preparation, health information technology can support pharmacists through a process of controls: checking whether the prescription is appropriate for the indication and the patient as well as facilitating contraindication checks such as allergies, drug interactions and conditions such as renal impairment which may necessitate a modification of the antibiotic dose. Electronic health record and ePrescribing systems can also support nurses during the administration of medication through reminders for timely administration as well as alerts for missed and delayed doses.…”
Section: Prompt Initiation Of Effective Treatment Supported By Electrmentioning
confidence: 99%